ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN PENGGUNA JASA KAPAL & BARANG DI PUSAT PELAYANAN SATU ATAP (PPSA) DIVISI RENDAL OPERASI PT IPC TERMINAL PETIKEMAS PERWAKILAN PONTIANAK - B31112071, DIEGO ATRIFANY (Jurnal Manajemen Update, 2016)
Changes in the business environment that has constantly evolving in harbor service industry is an opportunity for businesses today. This is a challenge for the providers of port services at the One-Roof Service Center of Rendal Operations Division PT IPC Container Terminal Pontianak Representatives in an effort to provide better service for the customers. This study aims to analyze how much influence the dimensions of service quality, which are the quality of technical, functional quality, corporate image on customer satisfaction in One-Roof Service Center Rendal Operations Division PT IPC Container Terminal Representative Pontianak. The population in this study is the overall service users of ships and good in One-Roof Service Center IPC Container Terminal Pontianak Representative who are still actively using ships and goods services. The sample in this study were 50 respondents using purposive sampling technique. Data analysis model used is the Multiple Linear Regression. Based on hypothesis testing using T test has been concluded that the three independent variables analyzed were proved significantly and affect partially on the dependent variable of customer satisfaction. Then through the F test found out that the variable of quality of technical, functional quality, and corporate image are simultaneously affect the dependent variable of customer satisfaction. Figure adjusted R Square, 0.770 shows that the dimensions of service quality is the quality of technical, functional quality and corporate image is able to explain collectively to the customer satisfaction in One-Roof Service Center IPC Container Terminal Pontianak Representative by 77%, while the rest are influenced by other variables not examined in this study. Keywords: service quality, quality of technical, functional quality, corporate image, customer satisfaction